2016
DOI: 10.1063/1.4945401
|View full text |Cite
|
Sign up to set email alerts
|

Mixed convection Jeffrey fluid flow over an exponentially stretching sheet with magnetohydrodynamic effect

Abstract: The steady two-dimensional MHD mixed convection boundary layer flow and heat transfer of a Jeffrey fluid over an exponentially stretched plate is investigated. The governing partial differential equations are first reduced to nonlinear ordinary differential equations, before being solved numerically using an implicit finite difference scheme. Local similarity solutions are obtained for some embedded parameters, such as Deborah number β, mixed convection parameter λ, Prandtl number Pr and Hartmann number H, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Also, the Jeffrey's fluid model approximates well the rheological behaviour of a wide range of industrial processes such as biotechnological detergents, physiological suspensions, dense foams, geological sediments, cosmetic creams, syrups, etc. Many researchers explored the industrial and biological flow problems using Jeffrey's model that include Katini Ahmad et al [12] investigated the magnetohydrodynamic mixed convection boundary layer flow and heat transfer of Jeffrey fluid past an exponentially stretching sheet. Saqib et al [13] reported the applications of Caputo-Fabrizio time-fractional derivatives to generalize the Jeffrey fluid past a vertical static plate.…”
Section: U Sir Is a DI Git Al C Oll E C Tio N Of T H E R E S E A R C mentioning
confidence: 99%
“…Also, the Jeffrey's fluid model approximates well the rheological behaviour of a wide range of industrial processes such as biotechnological detergents, physiological suspensions, dense foams, geological sediments, cosmetic creams, syrups, etc. Many researchers explored the industrial and biological flow problems using Jeffrey's model that include Katini Ahmad et al [12] investigated the magnetohydrodynamic mixed convection boundary layer flow and heat transfer of Jeffrey fluid past an exponentially stretching sheet. Saqib et al [13] reported the applications of Caputo-Fabrizio time-fractional derivatives to generalize the Jeffrey fluid past a vertical static plate.…”
Section: U Sir Is a DI Git Al C Oll E C Tio N Of T H E R E S E A R C mentioning
confidence: 99%
“…However, in this research 40 elements were observed in glutinous rice of mandotisalunkanan, kendenan and black glutinous rice ( Figure 5) with the XRF technique. 26 important elements have been detected in rice with several techniques [49,50]. From the research results, the determination of elements withfluorosence X-ray, 12 elements was detected, Fe and Cu is not found in all three types of glutinous rice.…”
Section: Crystallinitymentioning
confidence: 99%
“…A total of about 26 essential elements such as Al, Ca,Cu,S, N, Fe, K, Mg, Mn,Na, P,Ti, Si ,Cl,Ni, Mo and Zn have been detected in rice by several techniques [28] including X-ray flouresence and ICP. The presence of toxic elements and pesticide residues [29] is an other important and serious aspect of health. Atomic Absorption Spectrometry, inductively coupled plasma atomic emission spectrometry (ICP-OES), energy dispersive X-ray spectrometry and X-ray fluorescence techniques (XRF) are commonly used for the detection of the elements [30].…”
Section: Elemental Determination By Xrfmentioning
confidence: 99%